The Role of Listing Price Strategies on the Probability of Selling a House: Evidence from Vietnam - Bich Hong Nguyen Thi; Trong Hoai Nguyen; Thanh Hiep Truong (Real Estate Management and Valuation, 2020)
The aim of this paper is to measure the dynamic effects of listing price strategies and housing features on the probability of selling a house over the marketing period by adopting a two-stage regression analysis. In the first stage, we define the listing price strategies as the gaps between the actual listing price and expected selling price, estimated by a hedonic model. The Cox Probability Hazard models are applied in the second stage to measure the effects of listing price strategies on the probability of sales over various listing periods, such as 30-day, 90-day, 180-day and 270-day listing periods.